Special Remedial Work and Prophylaxis with Reference to Speech Disorders of Bilingual Children - Safonova, Natalya Mikhaylovna; Komarova, Lyubov Yurjevna; Zhytkova, Yulia Sergeevna; Zybina, Alesya Vladimirovna; Zakirova, Leysan Mudarisovna (Journal of History Culture and Art Research, 2019)
In the current modern education system, there is an inter-scientific integration of general didactics with pedagogical special remedial work. Regarding the development of children’s speech, this integration requires changes in the organizational structure of the general education process and becomes its systematizing factor which introduces innovations in learning technology. For the effective solution of this problem in teaching and education of a junior schoolchild with bilingualism it is necessary to introduce these innovative methods into the field of speech development. For this very reason in the 1990s, many scientists began working out specific technologies for the development of speech of junior schoolchildren. In a number of studies it has been noted that the main trend characterizing the image of modern education is integration of general educational and innovative areas in education. Integration is the most important means of education of children with speech difficulties: it modifies the organizational structure of the general educational process, and being a systematizing factor it performs a specific function in changing the learning technologies. Appraising the significance of this process it is necessary to notice that the integration introduces its own innovations. The technology of speech influence as a whole is a complex educational process with a new set of its own structural components, with extraordinary specifics, and moreover, it has definite prospects for further development. The practice guidelines we have examined do not limit the study of new technological solutions in creating our own model of the development of speech as a didactic system. The highlighting of other structural components is of great interest.